FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN SIKLUS MENSTRUASI PADA SISWI MADRASAH ALIYAH (MA) KOTA DENPASAR - Supriyadi, Yarssi Bumi Andini; Adhi, Kadek Tresna (ARCHIVE OF COMMUNITY HEALTH; Vol 12 No 1 (2025): April 2025DO - 10.24843/ACH.2025.v12.i01.p19, 2025)
ABSTRACT The menstrual cycle is a reproductive change that occurs in women during puberty, typically lasting for 28 days, with the majority of women having cycles between 25-30 days. Menstrual cycle disorders are classified as polimenorrhea, oligomenorrhea, and amenorrhea. Several factors that can influence the menstrual cycle include macronutrient intake, nutritional status, physical activity, stress levels, and macronutrient intake. Therefore, this study aims to determine the factors associated with the menstrual cycle among female students of Islamic Senior High Schools in Denpasar City. This cross-sectional research involved 80 students from grades X and XI, selected using a simple random sampling method. Data were collected through questionnaire responses related to physical activity variables, interviews regarding dietary intake to determine macronutrient intake variables, and anthropometric measurements to establish nutritional status variables. Data analysis was conducted using descriptive statistical tests and the chi-square test. The results of this study indicate that physical activity (p=0.017), stress levels (p=0.023), and nutritional status (p=0.028) are the most relevant variables. Female students are advised to maintain their BMI/U, balanced activity levels, and positive mindset for menstrual cycle prevention. Subsequent researchers should explore other factors such as infections, age of menarche, and micronutrient intake using a qualitative approach. Keywords: Macronutrient Intake, BMI/U, Physical Activity, Stress Level, Menstrual Cycle